KUALITAS PELAYANAN PUBLIK DALAM PENERAPAN APLIKASI E-PBB DI BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN PURWAKARTA - Rahmadanita, Annisa; Dowa, Pretty Petronella Clarita (Jurnal Teknologi dan Komunikasi Pemerintahan, 2021)
The purpose of the study was to obtain an overview of the quality of public services in the application of the E-PBB application at BAPENDA Purwakarta Regency. The research method used is descriptive qualitative. The findings of this study are in the tangible dimension, BAPENDA has been able to provide services that are not limited by space and time, but BAPENDA also provides physical facilities for services in utilizing the E-PBB application. In terms of reliability, the E-PBB application has been downloaded by the people of Purwakarta more than five thousand times, this shows that the people of Purwakarta Regency believe in the services provided by the district government. On the responsiveness dimension, the Purwakarta Regency Government is considered fast and precise in providing services. Meanwhile, in the assurance dimension, information was obtained that public service providers were friendly and courteous in providing services to the community. However, in the empathy dimension, there is no firm attitude taken by employees to meet the needs of the community so that tax payment services can be carried out directly by the community without having to come to the bank or payment location. The conclusion of the study is that BAPENDA Purwakarta Regency has made use of technology in making efforts to improve the quality of public services. The quality of public services provided by BAPENDA Purwakarta Regency is considered quite good, but still needs to maximize the features in the E-PBB application and consider the needs of the community, especially in terms of paying taxes that can be carried out directly. Keywords: Public Service Quality, E-Government, E-PBB